Improving surface sulfidization of azurite with ammonium bisulfate and its contribution to sulfidization flotation - Sheng, Qiuyue; Yin, Wanzhong; Yang, Bin; Cao, Shaohang; Sun, Haoran; Ma, Yingqiang; Chen, Keqiang (Minerals engineering, 2021)
[Display omitted] •The combined use of NH4HSO4 and Na2S reduced CO32– and OH– on azurite surface.•The combined use of NH4HSO4 and Na2S increased the floatability of azurite.•NH4HSO4 improved the surface sulfidization of azurite.•The adsorption of Na2S on azurite was strengthened by NH4HSO4 pretreatment. NH4HSO4 was used as an activator to improve the sulfidization flotation of azurite, with Na2S as the sulfiding agent and butyl xanthate (NaBX) as the collector. Microflotation, contact angle measurement, and adsorption test results indicated that NH4HSO4 facilitated the sulfidization flotation of azurite, enhanced the adsorption of Na2S, and improved the adsorption of NaBX, which increased the floatability of azurite. Further, X-ray photoelectron spectroscopy analysis demonstrated that the combined use of NH4HSO4 and Na2S decreased the amounts of CO32− and OH−, which resulted in high azurite surface hydrophobicity. In addition, NH4HSO4 increased the amount of copper sulfide and improved the sulfidation of azurite. A potential model for the reagent activation process was proposed. Density functional theory (DFT) calculations revealed that the interaction between the Na2S and azurite surface was strengthened by NH4HSO4 modification.